Epidemiological studies on Stemphylium vesicarium causing stemphylium blight disease of onion (Allium cepa) - GUPTA, R C; GUPTA, R P (The Indian Journal of Agricultural Sciences, 2014)
The experiment was conducted on epidemiological studies of Stemphylium vesicarium (Wallr.) Simmons causing stemphylium blight disease on onion (Allium cepa L.) variety Agrifound Light Red during rabi (winter) season, 2006-07, 2007-08 and 2008-09 at Research Farm, National Horticultural Research and Development Foundation, Nashik. Data of field studies revealed that stemphylium blight disease appeared during 5th standard week on onion crop under field conditions in consecutively three years in rabi season. The data shows a progressive increase and maximum percent disease index (PDI) of stemphylium blight was recorded in the 12th (24.50%), 14th (12.40% and 15th (13.15%) standard weeks during rabi season, 2006-07, 2007-08 and 2008-09 respectively. The average temperature ranged from 16.25°C to 22.5°C and relative humidity varied in between 85% to 90% was prevailed during 4th and 5th standard week during all the three years. Disease infection rate (r) lowers at the initial stage but increased progressively under congenial weather conditions. The data under disease progress curve (AUDPC) showed towards the disease pressure being higher in the year, 2006-07 followed by 2008-09 and 2007-08. Stepwise multiple regression equation was drawn for the disease prediction based on the data recorded consecutively three years by taking the average of percent disease index (PDI). The four weather parameters, viz. maximum temperature, minimum temperature, maximum RH and minimum RH were contributed in stemphylium blight disease prediction with 95.95 % precision during rabi season, 2006-07. Similarly, all the four weather parameters contributed for disease prediction with 75.56% and 77.33% precision during rabi season, 2007-08 and 2008-09 respectively. Thus the present findings can help for onion growers by alerting for prophylactic spray of fungicides to control the stemphylium blight and boost up the production.